Hyperprolactinaemia is common in Chinese premenopausal women with breast diseases - Zhu, Jiang; Tang, Yuyi; Lv, Cuixia; Cong, Han; Liu, Jie; Zhao, Song; Wang, Yawen; Zhang, Kai; Yu, Wenbin; Cai, Qian; Ma, Rong; Wang, Jianli (Frontiers in Genetics, 2023)
Abstract Purpose: Hyperprolactinaemia has been proposed to play a role in breast lesions pathophysiology. Thus far, controversial results have been reported for the relationship between hyperprolactinaemia and breast lesions. Moreover, the prevalence of hyperprolactinaemia in a population with breast lesions is scarcely reported. We aimed to investigate the prevalence of hyperprolactinaemia in Chinese premenopausal women with breast diseases, and explore the associations between hyperprolactinaemia with different clinical characteristics. Methods: This was a retrospective cross-sectional study performed in the department of breast surgery of Qilu hospital of Shandong University. Overall, 1461 female patients who underwent the serum prolactin (PRL) level assay before breast surgery from January 2019 to December 2020 were included. Patients were divided into two groups: before and after menopause. Data were analyzed using SPSS 18.0 software. Results: The results showed an elevated PRL level in 376 of the 1461 female patients with breast lesions (25.74%). Furthermore, the proportion of hyperprolactinemia among premenopausal patients with breast disease (35.75%, 340/951) was significantly higher than among postmenopausal patients with breast disease (7.06%, 36/510). In premenopausal patients, the proportion of patients with hyperprolactinaemia and the mean serum PRL level were significantly higher in those diagnosed with fibroepithelial tumours (FETs) and in younger patients (aged <35 years) than in those with non-neoplastic lesions and in those aged ≥35 years (both p<0.05). Conclusion: Hyperprolactinaemia is prevalent in Chinese premenopausal patients with breast diseases, especially in those with FETs, which implies a potential association, to some extent, between the PRL levels in various breast diseases.